2023
DOI: 10.1063/5.0111800
|View full text |Cite
|
Sign up to set email alerts
|

Switching boundary estimation and adaptive sliding mode control for the dynamical systems with discontinuity due to the actuators

Abstract: Due to the discontinuous physical property of the control actuators, the state space of such a dynamical system is divided into many subdomains. For each subdomain, the flow of such a system is governed by the corresponding subsystem. The state boundary between the adjacent subdomains is called the physical switching boundary. The controller is designed to switch when the subsystem of such a discontinuous dynamical system is switched in order to have the optimum control performance. Since the ambiguity and unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…They showed that the system undergoes a transition from periodic to chaotic motion. It has also been found that discontinuity in the physical property of a control actuator led to many subdomains in the state space of the dynamical system [ 25 ]. A study of a microbeam with geometric discontinuity under electrostatic load was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the system undergoes a transition from periodic to chaotic motion. It has also been found that discontinuity in the physical property of a control actuator led to many subdomains in the state space of the dynamical system [ 25 ]. A study of a microbeam with geometric discontinuity under electrostatic load was conducted.…”
Section: Introductionmentioning
confidence: 99%